Man, a Creature Unteachable. About the Prose Collection Dom Pre Jelena by Dominika MoravciKova - Urbanicova, Zuzana (Bohemica Olomucensia, 2024)
In this paper, we analyse a collection of short stories entitled Dom pre jelena (2002) by the author Dominika Moravcikova, who has already drawn attention to herself with her literary debut, a collection of poems, Deti Hamelnu (2020). In both collections, we can observe similar authorial practices, thematic focus, but also specifics analogous to a distinct movement in contemporary Slovak literature.
Keywords: Dominika Moravcikova; Dom pre jelena; contemporary Slovak prose